Development of E-Jobsheet on the Creation of Basic Patterns of Women's Pants Digitally Using the Canva Application - Umami, Septya Tri; Kharnolis, Mein; Arifiana, Deny; Yuniati, Mita (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
Describe the validity level of the E-Jobsheet for making digital women's pants patterns using the canva application at SMKN 2 Jombang so that it is suitable for use as learning media in terms of media experts, linguists and material experts. 2. Describe student learning outcomes after applying the E-Jobsheet for making women's pants patterns digitally using the canva application at SMKN 2 Jombang. This research is an R&D research with the ADDIE method. The subjects of this research were students of class XII Fashion 2 of SMKN 2 Jombang.  The results of this study are: 1) E-Jobsheet for making pants patterns digitally is declared feasible to use as learning media. This is evidenced by the results of media expert validity of 4.41 with a very valid category, material expert validity reached 3,59 with a very valid category and linguists reached 4.08 with a very valid category. The average of the three experts reached 4.02 with a very valid category. 2) The learning outcomes of students of SMKN 2 Jombang showed that 33 students were declared complete with a percentage of 100%. Thus, it can be concluded that the development of E-Jobsheet on making women's pants patterns digitally using the canva application in industrial fashion subjects contributes positively to improving student learning outcomes at SMKN 2 Jombang.